2014
DOI: 10.1007/s10549-014-2914-x
|View full text |Cite
|
Sign up to set email alerts
|

What lies behind chemotherapy-induced amenorrhea for breast cancer patients: a meta-analysis

Abstract: To evaluate the incidence of chemotherapy-induced amenorrhea (CIA) and its therapeutic impact in premenopausal breast cancer patients. A systematic search was performed to identify clinical studies that compared the incidence of CIA with different chemotherapy regimens and oncological outcomes with and without CIA. The fixed-effects and random-effects models were used to assess the pooled estimates. Heterogeneity and sensitivity analyses were performed to explore heterogeneity among studies and to assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 59 publications
0
48
0
Order By: Relevance
“…Based on the current study’s finding that endometrial cancer risks are increased for ER+PR+, ER+PR−, ER−PR+ breast cancers in the 40–49 age group, it is possible that the shared risk factors such as obesity, hormone replacement therapy, and reproductive factors may contribute to the elevated risk of endometrial cancer in these patients [2024]. Additionally, several studies have reported higher incidence of chemotherapy-induced amenorrhea (CIA) in premenopausal ER-positive breast cancer patients [2729]. The low estrogenic environment caused by chemotherapy along with tamoxifen treatment may lead to the activation and increased synthesis of endometrial estrogen and progesterone receptors, which may also contribute to increased risk of endometrial cancer [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current study’s finding that endometrial cancer risks are increased for ER+PR+, ER+PR−, ER−PR+ breast cancers in the 40–49 age group, it is possible that the shared risk factors such as obesity, hormone replacement therapy, and reproductive factors may contribute to the elevated risk of endometrial cancer in these patients [2024]. Additionally, several studies have reported higher incidence of chemotherapy-induced amenorrhea (CIA) in premenopausal ER-positive breast cancer patients [2729]. The low estrogenic environment caused by chemotherapy along with tamoxifen treatment may lead to the activation and increased synthesis of endometrial estrogen and progesterone receptors, which may also contribute to increased risk of endometrial cancer [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Although in the majority of studies recovery of menses occurs within 1 year, some patients may recover their menses within 3 years from EoC. Notably, whether taxanes increase CRA rates when added to anthracycline and cyclophosphamide-based regimens is still uncertain [56][57][58]. In terms of fertility, 1-year CRA and return of menses unreliably predict post-CT residual fertility potential [59]; however, pretreatment estimation of individual risk of residual ovarian reserve at the EoC could help tailor fertility preservation options for patients who require them.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected by the use of various definitions (that included amenorrhea in almost all cases) and timepoints of its evaluation in the different trials. However, amenorrhea is not an optimal surrogate marker for defining the gonadotoxicity of anticancer treatments [124,125]; the use of this endpoint is of particular concern when tamoxifen is given as adjuvant endocrine therapy considering the perturbation of menstrual function induced by the use of this treatment [126,127]. In the absence of a clear-cut definition, experts recommend to empirically define chemotherapy-induced POI with a composite definition of amenorrhea for ≥2 years and post-menopausal hormonal profile [6,128].…”
Section: Critical Appraisal Of the Available Clinical Evidencementioning
confidence: 99%